Comparing Glycemic Control of Children and Adolescents with Type 1 Diabetes on Multiple Daily Insulin Injection and those on Insulin Pump Therapy in limited resource Settings - Abdelghaffar, Shereen; Fahmy Abdou, Marise Antoun; Elsayed Elnemr, Samar Mohamad; Shamma, Radwa (Journal of Neonatal Surgery, 2025)
Background: Type 1 diabetes (T1D) is one of the most common chronic diseases in children. Overall, approximately 96,000 children under 15 years are estimated to develop type 1 diabetes annually worldwide. Aim of the work: To compare glycemic control of patients with (T1D) treated with different modalities, multiple daily injection (MDI) and continuous subcutaneous insulin infusion (CSII). Patients and Methods: This cross-sectional study was conducted on 30 patients diagnosed with T1D following at Diabetes & Endocrine Pediatric unit at Galaa Military hospital, patients were divided into two equal groups, group (A) 15 patients on MDI, group (B) 15 patients on CSII MiniMed paradigm 715 version. Not all patients were using continuous glucose monitoring (CGM), only 2 patients used flash glucose monitoring. Demographics, clinical data, and investigations were done with special emphasis on HbA1c at the beginning of the study, at three and six months. Results: The average blood glucose checks/day were significantly higher in patients on MDI (8.47 ± 1.68) than patients on pump (7.00 ± 1.36) with p-value = 0.014. There was statistically significant decrease in HbA1c level in patients on MDI after 6 months of glycemic control compared to that at the start of study and at 3 months with p-value < 0.001. However, there was a statistically significant increase in HbA1c level in patients on CSII after 6 months compared to that at start and at 3 months of the study with p-value < 0.001 Conclusion: Our study found no significant overall differences in glycemic control in the form of HbA1c between CSII and MDI therapy for children with T1D. It's clear that a pump with CGM will give the best glycemic index & more physiological treatment while a pump without CGM can give a false sense of security resulting in complications. So, for limited resource countries, CGM with MDI will be preferable over pump insertion without CGM